Structure and function of the open canalicular system – the platelet's specialized internal membrane network. (19th May 2018) - Selvadurai, Maria V.; Hamilton, Justin R.
Abstract: The open canalicular system (OCS) is an internal membrane structure found in platelets. First identified 50 years ago, the OCS comprises a tunneling network of surface-connected channels that appear to play an important role in platelet function. Yet, our understanding of how the OCS forms, how it functions, and what might regulate its structure and behavior remains fairly rudimentary. Structural abnormalities of the OCS are observed in some human platelet disorders. Yet, because platelets from these patients display multiple defects, the specific contribution of any OCS dysregulation to the impaired platelet function is unclear. However, recent studies have begun to shed light on mechanisms that regulate the OCS structure and to understand what influence the OCS has on overall platelet function. Advances in cellular imaging techniques have allowed whole-cell visualization of the OCS, providing the opportunity for a more detailed structural examination. Furthermore, recent work indicates that the modulation of the OCS structure may be sufficient to impact in vivo platelet function, opening up the intriguing possibility of manipulating the OCS structure as an anti-thrombotic approach. On the 50 th anniversary of its discovery, we review here what is known about OCS structure and function, and outline some of the key microscopy tools for studying this intriguing internal membrane system.